2020
DOI: 10.1002/cam4.2900
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of PET/CT uptake for peripheral clinical N0 non‐small cell lung cancer

Abstract: Objective In this cohort study, we determined the clinical value of the maximum standardized uptake value (SUVmax) of primary tumors in non‐small cell lung cancer (NSCLC). Study Design A retrospective review of NSCLC patients was performed from January 2011 to December 2017. Peripheral cN0 NSCLC patients with tumor size ≤2 cm were included. SUVmax was calculated as a continuous variable for semiquantitative analyses. A receiver operating characteristic curve was analyzed to assess the cutoff threshold of SUVma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…[11] also proved that this standard was uselessness in squamous cell carcinoma. In our subgroup analysis, we found that the cut-off values of SUV max and size of adenocarcinoma were smaller than those of squamous cell carcinoma, which was part consist with Wang’s research [8]. Besides, not all the peripheral cT1 NSCLC patients could get preoperative pathological results in China, and our research also confirmed that the pathological type was not an independent risk factor for peripheral cT1 NSCLC LNM.…”
Section: Discussionsupporting
confidence: 71%
“…[11] also proved that this standard was uselessness in squamous cell carcinoma. In our subgroup analysis, we found that the cut-off values of SUV max and size of adenocarcinoma were smaller than those of squamous cell carcinoma, which was part consist with Wang’s research [8]. Besides, not all the peripheral cT1 NSCLC patients could get preoperative pathological results in China, and our research also confirmed that the pathological type was not an independent risk factor for peripheral cT1 NSCLC LNM.…”
Section: Discussionsupporting
confidence: 71%
“…The remaining 16 full-text articles were assessed for eligibility and 2 articles were excluded due to insufficient data for the calculation of sensitivity and specificity of F-18 FDG PET or PET/CT for the prediction of OLNM in NSCLC patients. Finally, 14 studies were selected and were eligible for the systematic review and meta-analysis and no additional studies were found screening the references of these articles [13-26]. The characteristics of the included studies are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…All studies enrolled patients retrospectively. Eight studies came from China [14, 19, 21-26]. Other 6 studies were performed by non-China investigators [13, 15-18, 20].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations